2016
DOI: 10.18632/oncotarget.10689
|View full text |Cite
|
Sign up to set email alerts
|

Six plant extracts delay yeast chronological aging through different signaling pathways

Abstract: Our recent study has revealed six plant extracts that slow yeast chronological aging more efficiently than any chemical compound yet described. The rate of aging in yeast is controlled by an evolutionarily conserved network of integrated signaling pathways and protein kinases. Here, we assessed how single-gene-deletion mutations eliminating each of these pathways and kinases affect the aging-delaying efficiencies of the six plant extracts. Our findings imply that these extracts slow aging in the following ways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 102 publications
(114 reference statements)
1
28
0
Order By: Relevance
“…For example, Sargassum fusiforme was shown to protect against oxidative stress during ageing [ 21 ]. More recently, Lutchman reported six plant extracts that slow yeast ageing more efficiently than any known chemical compound [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sargassum fusiforme was shown to protect against oxidative stress during ageing [ 21 ]. More recently, Lutchman reported six plant extracts that slow yeast ageing more efficiently than any known chemical compound [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These six longevity-extending PEs are geroprotectors that postpone the onset and decelerate the progression of yeast chronological aging; each of them promotes a hormetic stress response and exhibits a different effect on a distinct set of longevity-defining cellular processes [86]. We have also demonstrated that PE4, PE5, PE6, PE8, PE12 and PE21 delay yeast chronological aging via an evolutionarily conserved network of signaling pathways and protein kinases (Supplementary Figure 1) [87]. Most of the six PEs slows down aging by modulating different nodes, edges and modules of this intricate network of longevity regulation (Supplementary Figure 1) [87]; some of these elements of the network are also under control of such naturally-occurring aging-delaying chemical compounds as spermidine and resveratrol (Supplementary Figure 1) [64, 67, 8894].…”
Section: Introductionmentioning
confidence: 99%
“…We have also demonstrated that PE4, PE5, PE6, PE8, PE12 and PE21 delay yeast chronological aging via an evolutionarily conserved network of signaling pathways and protein kinases (Supplementary Figure 1) [87]. Most of the six PEs slows down aging by modulating different nodes, edges and modules of this intricate network of longevity regulation (Supplementary Figure 1) [87]; some of these elements of the network are also under control of such naturally-occurring aging-delaying chemical compounds as spermidine and resveratrol (Supplementary Figure 1) [64, 67, 8894]. We noticed that, if a strain carrying an aging-delaying single-gene mutation affecting a certain node, edge or module of the network is exposed to some of the six PEs, the mutation and the PE enhance aging-delaying efficiencies of each other so that their combination has a synergistic effect on the extent of aging delay [87].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that cellular aging can be delayed and organismal longevity can be extended by some genetic, dietary and pharmacological interventions that attenuate certain pro-aging signaling pathways that control the rate of aging [2659]. These pro-aging signaling pathways operate as active mechanisms that (according to evolutionary theories of programmed aging) can limit organismal lifespan at a specific age.…”
Section: Introductionmentioning
confidence: 99%
“…due to lack of the evolutionary force [5, 6, 15, 17, 8288]. It was therefore concluded that the demonstrated ability of certain genetic, dietary and pharmacological interventions to extend lifespan in evolutionarily distant species by targeting mechanisms that actively limit organismal lifespan at a species-specific age [2659] validates evolutionary theories of programmed aging and invalidates evolutionary theories of non-programmed aging [5 - 17]. However, in all these cases the ability of genetic, dietary and pharmacological interventions to prolong organismal lifespan has been revealed under laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%